Условие задачи
Найдите \(h(4+x)+h(4-x),\) если \(h(x)=\sqrt[9]{x}+\sqrt[9]{x-8}. \)
Решение
\(h(x)\) - функция, \(h(x) = \sqrt[9]{x}+\sqrt[9]{x-8}.\) Например, \(h(1)=\sqrt[9]{1} + \sqrt[9]{1-8}.\)
\(h(4+x) = \sqrt[9]{4+x} + \sqrt[9]{x+4-8} = \sqrt[9]{4+x}+\sqrt[9]{x-4}\)
\(h(4-x) = \sqrt[9]{4-x} + \sqrt[9]{x-4-8} = \sqrt[9]{4-x}+\sqrt[9]{-x-4}\)
\(h(4+x) + h(4-x) = \sqrt[9]{4+x} + \sqrt[9]{x-4} - \sqrt[9]{x-4}-\sqrt[9]{x+4} = 0 .\)
Мы воспользовались тем, что \(\sqrt[9]{t}\) - нечётная функция
Ответ
0